GAMBARAN TINGKAT STRES MAHASISWA KEDOKTERAN BERDASARKAN MEDICAL STUDENT STRESOR QUESTIONNAIRE DI FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI - Siti Hediaty; Herlambang Herlambang; Nyimas Natasha Ayu Shafira (Journal of Medical Studies, 2022)
ABSTRACT Background: Stress can be interpreted as a pressure or something that makes individuals feel depressed. Stress can be influenced by the environment, competition with friends, financial circumstances and physical disorders such as disability. Stress can occur in individuals, groups, organizations and stressors from outside the organization. The influence of stress on medical students can be caused by various factors, namely financial problems, social demandSs, family demands and faculty demands. Objective: This study aims to describe the stress level of medical students at the Faculty of Medicine and Health Sciences Jambi University class 2017, 2018 and 2019. Methods: This research is a descriptive study with a cross sectional approach. The sample is 424 respondents. Data were collected using a medical student stressors questionnaire (MSSQ) which was modified for stress levels. Results: The results of the study of stress levels based on the frequency of stress events were 52.6% moderate stress. The level of academic-related stress is mostly in the category of severe stress with a range of 55%-56.6%. The level of stress related to intrapersonal and interpersonal relationships is mostly in the moderate stress category with a range of 37.1% - 50.0%. The level of stress related to learning relationships a lot in the moderate stress category with a range of 30.2% - 58.0% The stress level related to social relationships is a lot in the moderate stress category with a range of 29.0% - 68.0%. The level of stress related to desire and control a lot in the moderate stress category with a range of 30.8% - 47.6%. The level of stress related to group activities is mostly in the moderate stress category with a range of 52.2% - 56.0%.Conclusion: Based on the research, it can be concluded that most medical students at the Faculty of Medicine and Health Sciences, Jambi University experience moderate levels of stress. Keywords: Stress level, medical student, mssq. ABSTRAK Latar Belakang: Stress dapat diartikan sebagai suatu tekanan atau sesuatu yang membuat individu merasa tertekan. Stress dapat dipengaruhi dari lingkungan, persaingan dengan teman, keadaan finansial dan gangguan fisik seperti cacat. Stres dapat terjadi pada individual, kelompok, organisasi dan stressor dari luar organisasi. Pengaruh stress pada mahasiswa kedokteran dapat disebabkan berbagai factor yaitu masalah keuangan, tuntutan sosial, tuntutan keluarga dan tuntutan fakultas. Tujuan: Penelitian ini bertujuan untuk mengetahui gambaran tingkat stres mahasiswa kedokteran di Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi angkatan 2017, 2018 dan 2019. Metode: Penelitian ini merupakan penelitian deskriptif dengan pendekatan cross sectional. Sampel sebanyak 424 responden. Data dikumpulkan dengan menggunakan medical student stressors queisionare (MSSQ) yang telah dimodifikasi untuk tingkat stres. Hasil: Hasil penelitian tingkat stres berdasarkan frekuensi kejadian stres sebanyak 52,6% stres sedang. Tingkat stres terkait akademik banyak pada kategori stres berat dengan kisaran 55% - 56,6%. Tingkat stres terkait hubungan intrapersonal dan interpersonal banyak pada kategori stres sedang dengan kisaran 37,1% - 50,0%. Tingkat stres terkait hubungan belajar banyak pada kategori stres sedang dengan kisaran 30,2 % - 58,0% Tingkat stres terkait hubungan social banyak pada kategori stres sedang dengan kisaran 29,0% - 68,0 %. Tingkat stres terkait keinginan dan pengendalian banyak pada kategori stres sedang dengan kisaran 30,8% - 47,6%. Tingkat stres terkait aktivitas kelompok banyak pada kategori stres sedang dengan kisaran 52,2% - 56,0%. Kesimpulan: Berdasarkan penelitian dapat disimpulkan sebagian besar mahasiswa kedokteran di Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi mengalami stres tingkat sedang. Kata Kunci: Tingkat stres, mahasiswa kedokteran, mssq